Characteristics of Social and Administrative Sciences graduate programs and strategies for student recruitment and future faculty development in the United States. - Westrick SC; Kamal KM; Moczygemba LR; Breland ML; Heaton PC; Westrick, Salisa C; Kamal, Khalid M; Moczygemba, Leticia R; Breland, Michelle L; Heaton, Pamela C (Research in Social & Administrative Pharmacy, 2013)
Background: The rising demand of faculty in Social and Administrative Sciences (SAS) in pharmacy in the United States heightens the need to increase the number of Doctor of Philosophy (PhD) graduates in SAS who choose to pursue an academic career.Objectives: To describe the characteristics of SAS graduate programs and graduate students and identify strategies for student recruitment and future faculty development.Methods: An Internet survey (phase I) with key informants (graduate program officers/department chairs) and semistructured telephone interviews (phase II) with phase I respondents were used. Items solicited data on recruitment strategies, number of students, stipends, support, and other relevant issues pertaining to graduate program administration. Descriptive statistics were tabulated.Results: Of the 40 SAS graduate programs identified and contacted, 24 completed the Internet survey (response rate [RR]=60.0%) and, of these, 16 completed the telephone interview (RR=66.7%). At the time of the survey, the median number of graduate students with a U.S.-based PharmD degree was 3. An average annual stipend for graduate assistants was $20,825. The average time to PhD degree completion was 4.57 years, and approximately 31% of PhD graduates entered academia. Various strategies for recruitment and future faculty development were identified and documented.Conclusions: Findings allow SAS graduate programs to benchmark against other institutions with respect to their own achievement/strategies to remain competitive in student recruitment and development. Additional research is needed to determine the success of various recruitment strategies and identify potential new ones.